Community Empowerment on Recognizing the Risk of Diabetic Complications Through Self-Assessment - Joeliantina, Anita; Wuryaningsih, Sri Hardi; Hamid, Irfany Nurul; Proboningsih, Jujuk (Frontiers in Community Service and Empowerment, 2025)
Diabetes can cause complications in many parts of the body and can increase the risk of death. This community service activity aims to educate the community through community empowerment to prevent complications that may develop using self-assessment. The method used is to provide education to improve patient knowledge and self-assessment skills to avoid complications for patients with diabetes. The venue was the Menur Pumpungan Village Hall, Surabaya, where 20 participants attended. The flow of this community service activity is registration, health services, education, teaching how to recognize the risk of complications, and evaluation. Data on systolic blood pressure showed that 60% of participants had a ≥ value of 130 mmHg, while 20% had a diastolic blood pressure ≥ 100 mmHg. The abdominal circumference data of the participants showed that most had a circumference of > 80 cm in women. Data on BMI from 20 participants showed 55% had a BMI of more than 25. The blood sugar and cholesterol level data showed that some results had a value of ≥ 200 mg/dL, while partial uric acid levels were still ≥ 6. The data needs to receive attention and vigilance, so that the development of complications can be prevented or slowed down. Participants who participated in this community service activity have actively participated